Influence of Energy Balance and Glycemic Index on Metabolic Endotoxemia in Healthy Men. (2nd January 2017) - Breusing, Nicolle; Lagerpusch, Merit; Engstler, Anna Janina; Bergheim, Ina; Mueller, Manfred J.; Bosy-Westphal, Anja
Abstract : Objective : Overfeeding with a high-fat and/or high-carbohydrate (CHO) diet is known to increase plasma concentrations of endotoxin (lipopolysaccharide [LPS]) that may lead to metabolic disturbances like insulin resistance. The impact of CHO quality (i.e., the glycemic index [GI]) independent of fat intake on metabolic endotoxemia remains unclear. In the present study, the effects of changes in energy balance and GI on plasma endotoxin were studied. Methods : Fifteen healthy young men overconsumed diets containing 65% CHO and 20% fat for 1 week (OF; +50% of energy requirement) followed by 3 weeks of caloric restriction (CR; −50% of energy requirement) and were then randomized to 2 weeks hypercaloric refeeding (RF, +50% of energy requirement) with either a low- or high-GI (40 vs 74) diet. Results : During OF, subjects gained 1.9 ± 0.7 kg body weight (+0.6 ± 0.8% fat mass) followed by a weight loss of 6.1 ± 0.8 kg (−2.0 ± 0.6% fat mass) and weight regain of 4.0 ± 0.6 kg (0.9 ± 0.8% fat mass). Fasting insulin and homeostasis model assessment–insulin resistance (HOMAIR ) increased with OF and RF and decreased with CR, MatsudaISI decreased by 37% after RF (all p < 0.05). Endotoxin significantly increased by 30.8% with OF and by 24.7% with RF (both p < 0.05), whereas CR normalized endotoxin levels. No difference in endotoxin levels was observed between refeeding a hypercaloric high- or low-GI diet. Changes in endotoxin levels with RF were not related to changes in insulin sensitivity. Conclusion : A hypercaloric diet (OF and RF) increased plasma endotoxin irrespective of GI, whereas a negative energy balance did not reduce endotoxemia. Impaired insulin sensitivity with hypercaloric refeeding on a high-GI diet was not explained by metabolic endotoxemia.